Exploration of Javanese Traditional Birth Ceremonies: Perspectives on Form, Meaning, and Function - Wulandari, Desi; Waryanti, Endang; Muarifin, Moch.; Zargar, Nasir Ahmad (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2024)
In Javanese society, various symbolic actions such as wedding ceremonies, matchmaking, and mutual cooperation can be seen. The stages in this research include the preparation stage, implementation stage, and reporting stage, while the data sources in this research are in the form of words or actions of people who are interviewed or observed. The primary data source is notes from interviews and observations with sources. The offerings in implementing the series of baby birth procedures show that Javanese society hopes for the child's safety. Thus, it can be said that the meaning and function of the implementation of the tingkeban ceremony are: (1) to inherit the ancestral tradition so as not to be plagued by misfortune, and (2) to maintain balance, harmony, happiness, and safety life, which is a condition of peace without disturbance from other creatures or the surrounding environment. Essentially, this tradition asks for safety from God so that the child born is healthy and safe and always receives abundant sustenance.